2019
DOI: 10.1039/c9nj02245g
|View full text |Cite
|
Sign up to set email alerts
|

Release of reactive selenium species from phthalic selenoanhydride in the presence of hydrogen sulfide and glutathione with implications for cancer research

Abstract: The last decade has witnessed a renewed interest in selenium (Se) as an element able to prevent a range of illnesses in humans, mainly through supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Selenium (Se) is an essential trace element for humans, with multiple and complex effects on health, having antioxidant properties due to its presence in 25 selenoproteins in the form of selenocysteine amino acid [ 8 ]. Se compounds and H 2 S are present in living organisms and either alone or in combination interact with reactive oxygen species (ROS) [ 1 , 9 , 10 , 11 , 12 ]. In our previous work, we found that products of the sulfide/selenite (H 2 S/SeO 3 2− ) interaction scavenge superoxide-derived radicals, cleave plasmid DNA (pDNA) and modulate tonus of isolated rat aorta and blood pressure [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element for humans, with multiple and complex effects on health, having antioxidant properties due to its presence in 25 selenoproteins in the form of selenocysteine amino acid [ 8 ]. Se compounds and H 2 S are present in living organisms and either alone or in combination interact with reactive oxygen species (ROS) [ 1 , 9 , 10 , 11 , 12 ]. In our previous work, we found that products of the sulfide/selenite (H 2 S/SeO 3 2− ) interaction scavenge superoxide-derived radicals, cleave plasmid DNA (pDNA) and modulate tonus of isolated rat aorta and blood pressure [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[81,82] The study of the main cytotoxic mechanism is an intrinsically complex topic that may be the subject of future research. Also, the seleno-ligand is capable to breakdown and release highly toxic reactive selenium species (RSS) [33,83,84] The purposed mechanism is the radical generation coupled to the complex interaction with DNA or other interest biomolecules. The composition of mixed complexes could promote a multitargeting action mechanism and hence, activity against a wide range malicious agents as cancer cell lines, parasites and bacterial strains as seen previously in some multifunctional complexes.…”
Section: Cell Growth Inhibitionmentioning
confidence: 99%
“…Accordingly, phthalic selenoanhydride can interact with glutathione and hydrogen sulfide, scavenge free radicals such as superoxide (O 2 − ) and ˙cPTIO (2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide), and cleave pDNA. Interestingly, the sulfur or oxygen isosteres of phthalic selenoanhydride do not show these activities on their own, highlighting the role exerted by the selenium atom in these experimental activities [20].…”
Section: Introductionmentioning
confidence: 96%
“…Here, we explore the key ADMETox parameters for the 15 most promising selenoesters and selenoanhydrides (Figure 1), according to the biological activities assessed in previous works [18][19][20][21][22]. The selected in vitro assays cover fundamental physicochemical and biochemical properties of a drug candidate, such as solubility, cell membrane permeability (transporter effects), chemical and metabolic stability (specifically in the evaluation in human liver microsomes-HLMs), safety, and toxicology.…”
Section: Introductionmentioning
confidence: 99%